The showcase of salt rocks from Cardona in the Barcelona Natural Sciences Museum: conservation and adaptation for passive climate control - Marta Pérez Azcárate; Susana Duque Valero; Joan Ramon Aromi Folch; Marc Campeny Creco (Ge-conservación, 2023)
The results of the conservation work carried out on an exhibition set-up dating from the early twentieth century are presented. The exhibition set-up consists of a wooden showcase containing about twenty evaporite rocks from the collection of the Museu de Ciències Naturals de Barcelona (Spain). The work involved the remedial conservation of the rock specimens and showcase, and the improvement of the original environmental control system using sustainability criteria. An interdisciplinary team worked on the different phases of the project, which included prior historical and environmental studies. The remedial conservation of all elements in the collection has improved its accessibility and the monitoring of the environmental conditions of the new installation has confirmed the efficiency of the proposed passive environmental control system.